Temporal Evolution of Green Stormwater Infrastructure Strategies in Three US Cities - McPhillips, Lauren E.; Matsler, A. Marissa (Frontiers in Built Environment, 2018)
Over the last several decades, interest in green stormwater infrastructure (GSI) has rapidly increased, particularly given its potential to provide stormwater management in conjunction with other ecosystem services and co-benefits such as urban heat island mitigation or habitat provision. Here we explore the implementation of GSI in three US cities – Baltimore (Maryland), Phoenix (Arizona), and Portland (Oregon). We examine the trends in GSI construction over several decades, highlighting changes in implementation rates and GSI types with concurrent regulatory and economic changes. Additionally, we discuss the implications of these GSI portfolios for ecosystem service delivery in urban areas. Results indicate that Portland’s quantity of GSI is approximately ten times greater than the quantity of GSI in Phoenix or Baltimore. However, Baltimore has the most diverse portfolio of GSI types. In Phoenix, regional stormwater policies focused on flood control have led to retention basins being the dominant GSI type for decades. In contrast, Portland and Baltimore both have had substantial changes in their GSI portfolios over time, with transitions from detention or retention basins and underground facilities towards filters, infiltration facilities, and swales. These changes favor increased water quality function as well as provision of other ecosystem services. Additionally, we find evidence that each city followed a different GSI implementation pathway, with Portland’s combined sewer overflow program influencing initial development of GSI, while state legislation and regional water quality pressures played a major role in Baltimore’s GSI development. By studying the evolution of GSI in these different cities, we can see the variability in stormwater management trajectories and how they manifest in different suites of benefits. We hope that continued research of GSI implementation and performance will identify opportunities for future improvement of these infrastructures.